Agricultural development in a changing climate in Zambia: increasing resilience to climate change and economic shocks in crop production - Susanne Neubert; Michael Kömm; Axel Krumsiek; Annika Schulte; Nadine Tatge (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
Though Zambia is well endowed with natural resources, its agricultural sector is extremely underdeveloped, and almost half of the small-scale farmers do not even achieve food security. While internal political problems are a major cause for this, external disturbances such as climate change and economic shocks are additional threats to the sector. This study explores the main challenges and presents suggestions for resolutions based on empirical research. The e-voucher system, crop diversification and conservation agriculture belong to the bundle of suggested measures, which – when implemented together – could lead to pro-poor agricultural development. They would not only buffer climate and economic shocks but also increase income in a pro poor manner and show spill-over effects. Accompanied by suitable “software” measures at all levels in order to increase knowledge as well as adaptive and organisational capacity, farmers' resilience can be comprehensively strengthened. However, political will and more commitment from all stakeholders, including the engagement of the private sector and the self initiative of farmers, are needed to really make things happen.
Keywords: 330; Landwirtschaftliche Entwicklung; Agrarpolitik; Landwirtschaftliche Betriebsform; Klimawandel; Sambia